“This could be me”: exploring the impact of genetic risk for Huntington’s disease young caregivers - Dondanville, Danielle S. (J Community Genet, 2018)
Huntington’s disease (HD) is a predominantly adult-onset, genetic, neurodegenerative condition. Children of affected individuals have a 50% risk of inheriting HD and often assume caregiving roles for their parent. Studies specifically focused on HD young caregivers have proposed that the genetic risk component of HD “exacerbates” the caregiving experience and identified common responsibilities, burdens, and support needs, but none have explored the relationship between the caregiving role and perception of genetic risk. In an attempt to understand this relationship, we conducted a qualitative study to explore the interaction between a young caregiver’s perception of genetic risk, the caregiving experience, and thoughts about and plans for predictive testing. Thirteen individuals between 15 and 25 years who provided care for a parent with HD were recruited from two HD youth groups and local support groups. Interviews were recorded, transcribed, and analyzed thematically. Two themes emerged: (1) caregiving and thoughts about risk and (2) caregiving and perceived opinions towards genetic testing. Our findings suggest that the genetic risk colors the caregiving experience by evoking feelings about the future and a potential diagnosis of HD, in addition to impacting plans for predictive testing. Genetic counselors can use these findings to inform their understanding of caregiver experiences, which can aid them when helping patients explore their motivations for testing during a genetic counseling session. Future studies should explore the extent to which health care providers acknowledge the work of young caregivers in the home and provide support to these individuals.